(In-)Crease - Winka Dubbeldam (Oz, 2001)
(In)Crease/(En)Croach// Public/Private Traditionally the distinction between the public and the private was located at and limited to the front door or the facade. Today, a third condition proliferates; electronic space has introduced another public domain, de-localized in the infinite thickness of the screen.